Kolizyjny charakter orzeczeń Sądu Konstytucyjnego Ukrainy w zakresie opieki społecznej - Łaśko, Iryna (Przegląd Prawno-Ekonomiczny, 2013)
Streszczenie dostępne wyłącznie w języku angielskim: The activity of the Constitutional Court of Ukraine in the sphere of social security is not always consecutive. Considering the issue of the constitutionality of the legislative provisions that ceased or terminated the granting of privileges, compensations and guarantees to persons the Court has taken the opposite decisions. Such a conflict of decisions of the Constitutional Court of Ukraine does not provide a uniform understanding and application of the Constitution of Ukraine. The principle of reasonableness of decisions of the Constitutional Court of Ukraine as well as the security of the obligatoriness of the motivating part of it’s decisions at the next examination of the similar cases are important to solve this problem.